KAJIAN ASPEK PERILAKU PERATAAN LABA - DEASY ARIYANTI RAHAYUNINGSIH (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
Income smoothing is not against the rules but it is a tool to cover up dishonesty management. Financial statement containing information rekayasaan cause decreased reliability of financial reporting so that users can make mistakes when taking the decision was based on the profit that has been engineered. In this condition include accounting behavioral dimensions associated with the information produced by the accounting system. Accounting-related dimensions of human behavior is also concerned with the design, construction and use of an efficient system of accounting information